Mereduksi Stres Dalam Belajar Dengan Menggunakan Strategi Relaksasi - Sari, Ita Dian Arvita (Universitas Nusantara PGRI Kediri, 2020)
During the Covid-19 pandemic, everything must be done from home, including studying. There are many problems faced by students during Distance Learning (PJJ), which ultimately makes students experience stress in learning. Starting from students feeling bored studying at home, having difficulty concentrating, being anxious, restless when getting assignments from the teacher, causing dizziness/headaches, and reduced appetite. The problems above, if not resolved immediately, will have an impact on the value of student learning outcomes. One of the strategies to overcome this problem is a relaxation strategy. The purpose of this study was to determine that relaxation techniques can reduce stress in class XI MIPA 1 students of SMA Negeri 1 Mantua Lamongan, teaching 2020/2021. This research is single-subject research. This research lasted for 2 cycles, namely, cycle I and cycle II. Data collection techniques using interviews, observation, and measurement scale questionnaires. Methods of data analysis using qualitative and quantitative data analysis. The initial condition of the stress score reached 87.5, cycle I 75, while cycle II 47.5. From the results of the analysis, it can be concluded that there are differences in the stress levels of student learning before and after the action. Thus it can be concluded that relaxation strategies can reduce stress in learning for class XI MIPA 1 SMA Negeri 1 Mantap academic year 2020/2021.